Efeito terapêutico da fotobiomodulação nas lesões bucais de pacientes hospitalizados com COVID-19 - Santos, Juliana Mara Oliveira (2023)
Introduction: Oral manifestations COVID-19 patients are widely reported in the literature, with oral ulcers being the most common oral lesions. Laser therapy is a treatment for such injuries due to its analgesic, anti-inflammatory and healing effects. Therefore, the aim of the present study was to compare two different photobiomodulation protocols in the treatment of oral lesions of patients hospitalized with COVID-19. Materials and methods: An observational study divided into two phases, a retrospective and descriptive cross-sectional (evaluation of the prevalence of oral soft tissue lesions) and an interventional one (evaluation of the influence of photobiomodulation on the repair of oral soft tissue lesions) was carried out, which patients diagnosed with COVID-19, over 18 years of age, undergoing treatment at the Hospital Geral de Fortaleza (HGF) were included. The selected patients underwent laser therapy, after randomization to the application of protocol A (1J, R, point to point, without spacing) or protocol B (2J, R, with a spacing of 1 cm). Clinicopathological data such as age, length of stay, disease severity, comorbidities, therapeutic medications in use, use or not of mechanical ventilation, hemoglobin, leukocytes, platelets, C-reactive protein, D-dimer, type of oral lesion and conduct were collected. The assessment of the healing of oral lesions with photobiomodulation was carried out daily, at the bedside, using the following parameters: applied points, improvement or worsening in relation to the previous day and injury severity score. Data were expressed as absolute frequency and percentage or mean and standard deviation and compared using Fisher's exact test or Pearson's chi-square and Student's t and ANOVA/Bonferroni, respectively. Results: One hundred and ninety-two patients were included in the research, with the vast majority of oral lesions found in critical and severe patients (p=0.009). Antibiotic therapy was also related to a higher frequency of manifestations (p=0.020), as well as mechanical ventilation (p=0.009). Of the injuries evaluated, ulcers were the most prevalent (30.2%). Both photobiomodulation protocols proved to be effective in healing these injuries, with protocol A showing superiority in relation to protocol B.